Inhibition of Potato Tuber Invertase by an Endogenous Inhibitor: EFFECTS OF SALTS, pH, TEMPERATURE, AND SUGARS ON BINDING , - Anderson, Roger S. (1980)
Binding between potato tuber invertase and its endogenous inhibitor followed second-order reaction kinetics. Binding rates were diminished by the presence of various inorganic salts, MgCl(2) being especially effective. This effect of MgCl(2) was used in binding rate studies by adding the salt with sucrose to reduce binding during assay of previously unbound activity. The optimal pH for binding was about 4.8, similar to the optimal pH for catalytic activity of invertase. The optimal temperature for binding was about 45 C, approximately 5 C less than the optimum for catalytic activity. Sucrose at concentrations as low as 2 millimolar slowed binding; reducing sugars had little or no effect on binding or on catalytic activity.